Effect of Fe additive on the hydrogenation-dehydrogenation properties of 2LiH + MgB2/2LiBH4 + MgH2 system - Puszkiel, Julián Atilio (2015)
Lithium reactive hydride composite 2LiBH4 + MgH2 (Li-RHC) has been lately investigated owing to its potential as hydrogen storage medium for mobile applications. However, the main problem associated with this material is its sluggish kinetic behavior. Thus, aiming to improve the kinetic properties, in the present work the effect of the addition of Fe to Li-RHC is investigated. The addition of Fe lowers the starting decomposition temperature of Li-RHC about 30 °C and leads to a considerably faster isothermal dehydrogenation rate during the first hydrogen sorption cycle. Upon hydrogenation, MgH2 and LiBH4 are formed whereas Fe appears not to take part in any reaction. Upon the first dehydrogenation, the formation of nanocrystalline, well distributed FeB reduces the overall hydrogen storage capacity of the system. Throughout cycling, the agglomeration of FeB particles causes a kinetic deterioration. An analysis of the hydrogen kinetic mechanism during cycling shows that the hydrogenation and dehydrogenation behavior is influenced by the activity of FeB as heterogeneous nucleation center for MgB2 and its non-homogenous distribution in the Li-RHC matrix.